Comparison of infliximab with adalimumab in 827 biologic‐naïve patients with Crohn's disease: a population‐based Danish cohort study. Issue 5 (14th December 2017) - Singh, S.; Andersen, N. N.; Andersson, M.; Loftus, E. V.; Jess, T.
Summary: Background: There are conflicting data on comparative effectiveness of adalimumab and infliximab in patients with Crohn's disease (CD). Aims: To compare the effectiveness and safety of adalimumab and infliximab in biologic‐naïve patients with CD, in a nationwide register‐based propensity score‐matched cohort study in Denmark. Methods: A total of 2908 Danish adults with CD had been treated with adalimumab or infliximab as their first biologic agent between 2005‐2014. By Cox regression, we compared rates of all‐cause hospitalisation, CD‐related hospitalisation, major abdominal surgery and serious infections after variable 2:1 propensity score matching, accounting for baseline disease characteristics, healthcare utilisation and use of CD‐related medications. Results: After propensity‐score matching, we included 315 adalimumab‐ (34.9 ± 12.9 years, 41.9% males) and 512 infliximab‐treated (33.6 ± 12.6 years, 40.8% males) patients, with median disease duration 4.0 years; 36.9% had prior abdominal surgery. Over a median follow‐up 2.3 years after starting biological therapy, there were no significant differences in rate of CD‐related hospitalisation (hazard ratio [HR], 0.81 [95% CI, 0.55‐1.20]) or major abdominal surgery (HR, 1.24 [0.66‐2.33]) between adalimumab‐ and infliximab‐treated patients, though rate of all‐cause hospitalisation was lower in adalimumab‐treated patients (HR, 0.74 [0.56‐0.97]). There was no significant difference in incidence of serious infections requiring hospitalisation (HR, 1.06 [0.26‐4.21]). These results were stable in patients treated with biological monotherapy (all‐cause hospitalisation: HR, 0.75 [0.53‐1.05]; CD‐related hospitalisation: HR, 0.82 [0.51‐1.32], abdominal surgery: HR, 1.47 [0.63‐3.47]) or in combination with immunomodulators (all‐cause hospitalisation: HR, 0.70 [0.44‐1.11]; CD‐related hospitalisation: HR, 0.80 [0.42‐1.52], abdominal surgery: HR, 1.02 [0.39‐2.64]). Conclusions: In this population‐based, propensity score matched, real‐life cohort study using administrative claims, there was no significant difference in effectiveness and safety of adalimumab and infliximab in biologic‐naïve patients with CD. Abstract : Linked Content This article is linked to Lim et al paper. To view this article visithttps://doi.org/10.1111/apt.14549 .